PARADIGM OF ENVIRONMENTAL PROTECTION AND MANAGEMENT OF HOUSEHOLD MEDICAL WASTE IN THE COVID-19 PANDEMIC: EXPECTATIONS AND CHALLENGES - Serlika Aprita; Hasanal Mulkan (Awang Long Law Review, 2023)
The Covid-19 outbreak has had an impact on various sectors of life, including the environment. Medical waste in the community has increased in the new normal era of the Covid-19 pandemic, this can be seen from the existence of new adaptations in society, but in its application, household medical waste management is still an obstacle to this day. The approach method used is juridical-normative, with the type of dogmatic research, a form of perscriptive research on legal relations. The specification of this research is descriptive-analytical, the government continues to make various efforts in handling household medical waste. State responsibility as the basis for the implementation of environmental protection and management is carried out through the enforcement of environmental laws, namely administrative, civil and criminal law enforcement. Formulation of a new policy on the management of Infectious and Household Waste from Handling Covid 19.